Regulasi Poligami Dalam Pendekatan Maqashid As-Syari’ah - Ach Syaifur Rizal; Samsul Arifin; Ahmad Rezy Meidina (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Ach Syaifur Rizal, Fakultas Syariah dan Hukum Universitas Islam Negeri Sunan Kalijaga syaifurrizal926@gmail.com , ABSTRACT Islamic Islamic law aims to organize human life better so that every law that is prescribed must have a purpose. Therefore, the existence of marriage law must have a purpose. From several meanings of marriage, marriage has a very noble purpose, namely to form a sakinah mawaddah warahmah family. However, this noble purpose of marriage is widely misunderstood for those who want to practice polygamy. Polygamy is interpreted only as a biological distribution of sex, meaning that it only fulfills sexual needs. Whereas the purpose of polygamy is to maintain and elevate the status of a woman by looking at the large number of women who are not comparable to men. From some people who abuse polygamy, whether they understand the concept of polygamy or not, we are still trying to give them an understanding of the good concept of polygamy so that women are not used as a layer for their desires to channel their biology. We are here to focus on how the concept of polygamy according to classical and contemporary ulama', where the results of their thoughts are implied in the form of a law known as the marriage law in Indonesia. And to increase the data, we use quantitative data here by comparing the thoughts between classical scholars and contemporary scholars about the concept of polygamy. in the concept of polygamy which delivers to families who are sakinah mawaddah warhamah. Keywords : Marriage, Polygamy and Maqashid As-Shari'ah